Gagasan Pembentukan Peradilan Khusus Pilkada Dalam Mewujudkan Electoral Justice - Pratama, Surya Mukti; Nurlela, Ela; Dynantheo Sitepu , Hendry Gian (Fakultas Hukum Universitas Surabaya, 2021)
General Election and Regional Election are two different things on a constitutional basis. Then it was strengthened and confirmed by the decision of the Constitutional Court No. 97 / PUU / XI / 2013. This condition encourages the author to discuss the urgency of establishing a special election court with a simultaneous regional election system and a special court format that is effective in realizing electoral justice. This article aims to discuss the problems faced in resolving regional election results disputes in order to realize electoral justice in regional elections. The juridical formation of a special regional elections judicial body is an urgent need because it is a mandate of the law that must be implemented. The regional elections court format in realizing electoral justice includes three important principles that must be possessed by the regional elections court, the status and position of the regional elections court, the regional elections court judges, the role of the Supreme Court as judex juris and is attributed the authority to review the decision of the regional elections special court and relate to absolute competence. from the regional elections court.